Medieval Paris - Tartaglino, Anna Cazzini; Torcellan, Nanda 1934- (Austin, TX : Raintree Steck-Vaughn, 2001)
A guide to medieval Paris uses a tour of the city to examine how people lived and worked there.
Includes index
9 - 12 years
Keywords: Middle Ages -- History; Paris (France) -- History -- To 1515; Paris (France) -- Social life and customs; France -- History -- Medieval period, 987-1515.